A Novel Monocyte Subset as a Unique Signature of Atherosclerotic Plaque Rupture - Vinci, Ramona; Pedicino, Daniela; Bonanni, Alice; D’Aiello, Alessia; Severino, Anna; Pisano, Eugenia; Ponzo, Myriana; Canonico, Francesco; Ciampi, Pellegrino; Russo, Giulio; Di Sario, Marianna; Montone, Rocco Antonio; et al. (Frontiers in Cell and Developmental Biology, 2021)
The evaluation of monocyte subset distribution among acute coronary syndrome (ACS) patients according to culprit coronary plaque morphology has never been explored. We evaluated whether there were significant differences in frequency of circulating monocyte subsets isolated from ACS patients according to optical coherence tomography (OCT) investigation of plaque erosion and rupture. We enrolled 74 patients with non-ST-elevation ACS (NSTE-ACS), 21 of them underwent OCT investigation of the culprit coronary plaque and local macrophage infiltration (MØI) assessment. As control, we enrolled 30 chronic coronary syndrome (CCS) patients. We assessed the frequency of monocyte subsets in the whole study population, in reliance on their CD14 and CD16 expression (classical, CM: CD14++CD16–; intermediates, IM: CD14++CD16+; non-classical, NCM: CD14+CD16++). Then, we tested the effect of lipopolysaccharide (LPS) (a CD14 ligand) on peripheral blood mononuclear cells (PBMCs) of NSTE-ACS patients, quantifying the inflammatory cytokine levels in cell-culture supernatants. Our data proved that monocyte subsets isolated from NSTE-ACS patients represent a peculiar biological signature of the pathophysiological mechanism lying beneath atherosclerotic plaque with a ruptured fibrous cap (RFC) as compared with plaque erosion. Moreover, the magnitude of LPS-mediated effects on IL-1β, IL-6, and IL-10 cytokine release in cell-culture supernatants appeared to be greater in NSTE-ACS patients with RFC. Finally, we described a fourth monocyte population never explored before in this clinical setting (pre-classical monocytes, PCM: CD14+CD16–) that was prevalent in NSTE-ACS patients as compared with CCS and, especially, in patients with RFC and culprit plaque with MØI.